THU0304 Gross Cystic Disease Fluid Protein-15(GCDFP-15)/Prolactin-Inducible Protein (PIP): A Functional Salivary Biomarker for Primary SjöGren's Syndrome?. (23rd January 2014) - Baldini, C.; Martini, D.; Sernissi, F.; Gallo, A.; Rossi, C.; Mosca, M.; Santini, E.; Pepe, P.; Solini, A.; Perez, P.; Alevizos, I.; Bombardieri, S.
Abstract : Background: Gross cystic disease fluid protein-15(GCDFP-15)/prolactin-inducible protein (PIP) is a secretory acinar glycoprotein of 14KDa which has been recently described as significantly lower in salivary samples of patients with primary Sjögren's syndrome (pSS) in comparison to healthy volunteers. Although the function of GCDFP-15/PIP remains unknown, recent observations have shown that GCDFP-15/PIP may bind to the C-terminal portion of aquaporin 5 (AQP5), potentially interfering with the salivary secretion processes. Objectives: 1) to investigate the expression of GCDFP-15/PIP in whole saliva of patients with pSS in comparison to healthy volunteers and patients with no-SS sicca syndrome 2) to quantify GCDFP-15/PIP mRNA expression levels in the MSGs of pSS patients and subjects with no-SS sicca syndrome 3) to correlate the expression of GCDFP-15/PIP with the salivary flow rate of the subjects enrolled in the study in order to verify whether GCDFP-15/PIP salivary reduction could be related to the pSS exocrinopathy Methods: Consecutive patients with a diagnosis of pSS (AECG criteria) were enrolled in this proof of concept study. The control group consisted of subjects with suspected SS who did not fulfill the AECG criteria for pSS and healthy volunteers. Unstimulated whole saliva will be collected under standard conditions at the study inclusion according to the AECG sialometry protocol. The expression of GCDFP-15/PIP in whole saliva of pSS patients and control subjects was assessed by Western Blot (WB) with a rabbit monoclonal antibody to GCDFP-15/PIP amino-terminal end (Abcam). The analysis of GCDFP-15/PIP gene expression in MSGBs was performed by real-time PCR on an ABI PRISM 7900 sequence detector (Applied Biosystems) while immunohistochemistry analysis was carried out with a goat polyclonal to GCDFP-15/PIP (Abcam). For statistical comparisons, t-test and Spearman's correlation were employed; p-values <0.05 were considered significant. Results: Forty-two pSS patients and 17 no-SS sicca controls and 13 healthy subjects were included in this study. WB analysis confirmed the significant decrease of GCDFP-15/PIP in whole saliva of pSS in comparison with both healthy volunteers (p=0.003) and no-SS sicca control subjects (p=0.02). GCDFP-15/PIP mRNA and immunoistochemistry results confirmed the significant decrease of GCDFP-15/PIP also in the MSGs of pSS patients in comparison with no-SS sicca controls (p <0.05). Both GCDFP-15/PIP mRNA levels in MSGs (r=0.66, p=0.004) and GCDFP-15/PIP levels in saliva samples (r=0.30, p=0.02) were significantly correlated with the salivary flow rate of the subjects enrolled in this study. Conclusions: This proof of concept study confirmed the reduction of GCDFP-15/PIP in the MSGs and whole saliva of patients with a diagnosis of pSS. The correlation between GCDFP-15/PIP and the subjects' salivary flow rate may suggest a potential functional role for this protein in the alteration of the salivary secretion processes in pSS. Additional studies are required to better clarify whether these preliminary data have any implication for pSS pathogenesis and treatment. Disclosure of Interest: None Declared